Brain-Computer Interface and Silent Speech Recognition on Decentralized Messaging Applications - Lourenço, Fábio André Vilar (2021)
Online communications have been increasingly gaining prevalence in people’s daily lives, with its widespread adoption being catalyzed by technological advances, especially in instant messaging platforms. Although there have been strides for the inclusion of disabled individuals to ease communication between peers, people who suffer hand/arm impairments have little to no support in regular mainstream applications to efficiently communicate with other individuals. Moreover, a problem with the current solutions that fall back on speech-to-text techniques is the lack of privacy when the usage of these alternatives is conducted in public. Additionally, as centralized systems have come into scrutiny regarding privacy and security, the development of alternative decentralized solutions has increased by the use of blockchain technology and its variants. Within the inclusivity paradigm, this project showcases an alternative on human-computer interaction with support for the aforementioned disabled people, through the use of a braincomputer interface allied to a silent speech recognition system, for application navigation and text input purposes, respectively. A brain-computer interface allows a user to interact with the platform just by though, while the silent speech recognition system enables the input of text by reading activity from articulatory muscles without the need of actually speaking audibly. Therefore, the combination of both techniques creates a full hands-free interaction with the platform, empowering hand/arm disabled users in daily life communications. Furthermore, the users of the application will be inserted in a decentralized system that is designed for secure communication and exchange of data between peers, enforcing the privacy concern that is a cornerstone of the platform.